92.5k views
2 votes
X-1+x(x-1)=3(x-1)

Please solve for x

User Ranie
by
5.2k points

2 Answers

3 votes

x-1+x(x-1)=3(x-1)

x^2-1=3x-3

x^2-3x+2=0

Factor: (x-1)(x-2)=0

Set factors equal to 0:

x-1=0 and x-2=0

x=1 or x=2

User Cwc
by
5.2k points
5 votes

Factor out x-1.

... (x-1)(1 + x) = 3(x-1)

... (x-1)(x +1 -3) = 0 . . . . subtract the right side

... (x -1)(x -2) = 0 . . . . . . simplify

... x = 1 . . . or . . . x = 2 . . . . use the zero-product rule*

_____

* A product is only zero when one or more of its factors is zero.

User Jerad Rutnam
by
4.4k points